2006
DOI: 10.1002/ptr.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spirulina on the number of ovary mast cells in lead‐induced toxicity in rats

Abstract: The present study investigated the protective effect of Spirulina against the lead-induced increase in mast cells in the ovary during the oestrous cycle of rats. In the ovary cortex and medulla of lead-exposed animals, there was a significant increase in the number of mast cells; however, when also treated with Spirulina, a decrease was observed. The number of mast cells when Spirulina (300 mg/kg) was used alone was not significantly different from that of the control group. These results indicate that Spiruli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Additionally, the recipients were treated with steroids and MCs are known for their susceptibility to the action of hormones like estradiol and progesterone (Wordinger et al, 1985; Cocchiara et al, 1992; Rudolph et al, 2004; Jensen et al, 2010) which probably induced the expansion of the MCs present in the ovaries and their migration to the uterus. We detected high amounts of MCs within the ovaries (unpublished observations) that coincides with observations done in different species like mouse (Skalko et al, 1968), rat (Jones et al, 1980; Gaytan et al, 1991; Aydin et al, 1998; Batth and Parshad, 2000), hamster (Shinohara et al, 1987; Krishna and Terranova, 1991), cow (Reibiger and Spanel-Borowski, 2000), goat (Karaca and Simşek, 2007; Karaca et al, 2008), and chicken (Parshad and Kathpalia, 1993). Furthermore, we could not find alterations in the number of follicles as well as corpora lutea between MC-deficient W-sh and control mice (Woidacki et al, 2013).…”
Section: Mast Cells Are Important For Induction and Maintenance Of Prsupporting
confidence: 89%
“…Additionally, the recipients were treated with steroids and MCs are known for their susceptibility to the action of hormones like estradiol and progesterone (Wordinger et al, 1985; Cocchiara et al, 1992; Rudolph et al, 2004; Jensen et al, 2010) which probably induced the expansion of the MCs present in the ovaries and their migration to the uterus. We detected high amounts of MCs within the ovaries (unpublished observations) that coincides with observations done in different species like mouse (Skalko et al, 1968), rat (Jones et al, 1980; Gaytan et al, 1991; Aydin et al, 1998; Batth and Parshad, 2000), hamster (Shinohara et al, 1987; Krishna and Terranova, 1991), cow (Reibiger and Spanel-Borowski, 2000), goat (Karaca and Simşek, 2007; Karaca et al, 2008), and chicken (Parshad and Kathpalia, 1993). Furthermore, we could not find alterations in the number of follicles as well as corpora lutea between MC-deficient W-sh and control mice (Woidacki et al, 2013).…”
Section: Mast Cells Are Important For Induction and Maintenance Of Prsupporting
confidence: 89%
“…Spirulina (Sp), a blue-green algae, has been demonstrated as an antioxidant and antiapoptotic in many in vitro and in vivo studies [12]. Its protective effects on the rat ovary against lead-induced [13] and Cyc-induced toxicities has been published [14]. However, no reports are available on the biochemical effects of Cyc on the ovary or the possible protective effects of Sp on ovarian histomorphometry and oxidant status in Cyc-exposed ovaries.…”
Section: Introductionmentioning
confidence: 99%
“…However, no significant changes in Pb levels were observed in the liver, lung, heart and kidneys of the two animal groups. The administration of 300 mg/kg of Spirulina was also able to diminish the increase in the number of mast cells due to Pb in the cortex and medulla of adult inbred female Wistar albino rat ovaries during the oestrous cycle [128]. Ponce-Canchihuamán et al ( 2010) [129] demonstrated that Spirulina restored the biochemical parameters of the liver and kidneys in old Wistar male rats, decreasing the lipid levels both in plasma and liver as well as lipid peroxidation in the liver and kidneys.…”
Section: Spirulinamentioning
confidence: 90%